Identification of growth related quantitative Trait Loci within the abalone using comparative microsatellite bulked segregant analysis - Slabbert, Ruhan (Stellenbosch : Stellenbosch University, 2010)
Thesis (PhD (Genetics))--Stellenbosch University, 2010.